Senses of Landscape - Sallis, John, 1938- (Book collections on Project MUSE., 2015)
Beginning with the assertion that earth is the elemental place that grants an abode to humans and to other living things, in Senses of Landscape the philosopher John Sallis turns to landscapes, and in particular to their representation in painting, to present a poweru00ADful synthetic work. Senses of Landscape proffers three kinds of analyses, which, though distinct, continually intersect in the course of the book. The first consists of extended analyses of distinctive landscapes from four exemplary painters, Paul Cezanne, Caspar David Friedrich, Paul Klee, and Guo Xi. Sallis then turns to these artu00ADistsu2019 own writingsu2014treatises, essays, and lettersu2014about art in general and landscape painting in particular, and he sets them into a philosophical context. The third kind of analysis draws both on Sallisu2019s theoretical writings and on the canonical texts in the philosophy of art (Kant, Schelling, Hegel, and Heidegger). These analyses present for a wide audience a profound sense of landscape and of the earthly abode of the human.